2014
DOI: 10.1371/journal.pone.0096645
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Factors and Prejudice toward HIV and Hepatitis B/C Status in a Working-Age Population: Results from a National, Cross-Sectional Study in Japan

Abstract: BackgroundIn many countries, HIV, hepatitis B virus (HBV), and hepatitis C virus (HCV) infected individuals may face discrimination and mistreatment from coworkers. Effective interventions to reduce workplace discrimination are therefore needed to protect these vulnerable populations. The current study investigated potential associations between sociodemographic factors and prejudice toward HIV and HBV/HCV infected colleagues within a Japanese working population.MethodsAn online anonymous, nationwide internet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
(29 reference statements)
2
18
2
Order By: Relevance
“…This result confirms the results from a study of Japan's working population, 22 although the Japanese study Note. The basis outcome is mild or without discrimination.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result confirms the results from a study of Japan's working population, 22 although the Japanese study Note. The basis outcome is mild or without discrimination.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with a previous study in Japan that also found no association between gender and prejudice toward HIV, HBV or HCV-infected people. 22 No previous study has assessed the influence of education on HBV-related discrimination, although a previous study found Chinese providers with a higher medical education tended to show high levels of discrimination against HIV patients. 21, 23 We hypothesized that rural migrant workers' education status was associated with HBV-related discrimination, but our results did not confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was inconsistent with a previous study in Japan showing that gender was unassociated with prejudice toward HIV-, HBV-, or HCV-infected colleagues. 21 In the current study, our hypothesis was that income was associated with HBV-related discrimination, but the results were in striking contrast to the hypothesis. Participants' discrimination levels did not significantly differ based on income.…”
Section: Discussioncontrasting
confidence: 89%
“…This is contrary to the finding that older age was associated with decreased prejudice toward HBV-or HCV-infected colleagues in the Japanese study. 21 We found that individuals with higher education tended to have less severe discrimination compared with those with less education (the reference education group), and the severe discrimination rate of those with a medium education level did not differ from that of the low education group. No previous study has assessed the influence of education on HBV-related discrimination, although a study in China showed that providers with higher medical education tended to show higher levels of discrimination against those with HIV.…”
Section: Discussionmentioning
confidence: 57%
“…A qualitative study on the causes of diffidence among mid-level public health nurses who were supporting people with mental disorders identified seven categories of causes, such as a lack of experience and problems with developing a perspective regarding their particular field [15]. Additionally, old age might be a factor, as evidenced by a nationwide Internet survey on prejudice toward individuals with HIV or hepatitis B and C among the working-age population of Japan [16]. A study in Taiwan showed that nurses with longer careers, self-labels of "absolute heterosexual," and high religiousness were more likely to have negative attitudes towards homosexuality [17].…”
Section: Introductionmentioning
confidence: 99%